2014
DOI: 10.1007/s12149-014-0811-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of septic pulmonary embolism associated with renal abscess mimicking pulmonary metastases of renal malignancy

Abstract: We report the case of a 46-year-old woman with acute febrile symptom who had multiple pulmonary nodules and a renal mass. She underwent (18)F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) to find a hidden malignancy and the cause of her fever. FDG PET/CT images demonstrated a renal mass and multiple lung nodules with intense FDG uptake, which was suspicious of a renal malignancy with multiple pulmonary metastatic lesions. CT-guided biopsies of the pulmonary and renal lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Sometimes, systemic antibiotics or chemotherapy treatment and short-term follow-up are necessary to differentiate abscess versus metastases. Similarly, focal renal infections like renal tuberculosis, acute pyelonephritis, xanthogranulomatous pyelonephritis, and renal abscesses have all been encountered on 18F-FDG PET/CT and may be mistaken for a neoplastic process [46][47][48][49]. Gonadal infection such as tubo-ovarian abscesses and orchitis has been mistaken for neoplasm on 18F-FDG PET/CT [50][51][52].…”
Section: Abdomen and Pelvismentioning
confidence: 99%
“…Sometimes, systemic antibiotics or chemotherapy treatment and short-term follow-up are necessary to differentiate abscess versus metastases. Similarly, focal renal infections like renal tuberculosis, acute pyelonephritis, xanthogranulomatous pyelonephritis, and renal abscesses have all been encountered on 18F-FDG PET/CT and may be mistaken for a neoplastic process [46][47][48][49]. Gonadal infection such as tubo-ovarian abscesses and orchitis has been mistaken for neoplasm on 18F-FDG PET/CT [50][51][52].…”
Section: Abdomen and Pelvismentioning
confidence: 99%
“…The primary infectious sites of SPE include right-sided IE, pelvic thrombophlebitis, head and neck infections, vascular catheters, implantable devices, and soft tissue infections [2,4]. The risk factors for SPE include intravenous drug use, catheter insertion, and diabetes mellitus [5]. In addition, in the single-center retrospective analysis of 40 SPE patients, up to 25% of patients (10 patients) were hemodialysis patients [4]; thus, hemodialysis may be a risk factor for SPE.…”
Section: Discussionmentioning
confidence: 99%
“…Only three cases of renal abscess as a primary source of SPE have been reported 30 – 32 . In the present study, we reported two cases of renal abscess as a primary source of SPE.…”
Section: Discussionmentioning
confidence: 99%